2021
DOI: 10.1136/thoraxjnl-2021-217160
|View full text |Cite
|
Sign up to set email alerts
|

Use of inhaled corticosteroids and risk of acquiringPseudomonas aeruginosain patients with chronic obstructive pulmonary disease

Abstract: BackgroundInhaled corticosteroids (ICS) are commonly used to treat COPD and are associated with increased risk of pneumonia. The aim of this study was to assess if accumulated use of ICS is associated with a dose-dependent risk of a positive airway culture with Pseudomonas aeruginosa in patients with COPD.MethodsWe conducted a multiregional epidemiological cohort study including Danish COPD patients followed in outpatient clinics during 2010–2017. ICS use was categorised based on accumulated prescriptions rede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
2
15
0
2
Order By: Relevance
“…Therefore, the long-term treatment of COPD patients with ICS might have blunted the normal response that is orchestrated by alveolar macrophages after PA infection, both in terms of TLR2 expression and effective cytokine production, impairing the management of the infectious process. This observation supports the finding in the clinical studies of Eklöf et al [ 15 ] and Shafiek et al [ 5 ], who found that high doses of ICS could be a risk factor for PA in severe COPD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the long-term treatment of COPD patients with ICS might have blunted the normal response that is orchestrated by alveolar macrophages after PA infection, both in terms of TLR2 expression and effective cytokine production, impairing the management of the infectious process. This observation supports the finding in the clinical studies of Eklöf et al [ 15 ] and Shafiek et al [ 5 ], who found that high doses of ICS could be a risk factor for PA in severe COPD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, in line with our data, a recent study by Eklöf et al found that ICS was a risk factor for acquiring PsA infection as a dose-dependent risk compared with those not using ICS in severe COPD Danish cohort. 38…”
Section: Open Accessmentioning
confidence: 99%
“…In addition to the increase in local adverse effects observed in the aforementioned clinical studies, the use of ICSs was generally associated with an increased likelihood of acquiring an infection with P. aeruginosa or non-tuberculous mycobacteria and developing pneumonia, at least in certain subgroups of COPD patients, especially those with lower eosinophil counts [ 102 104 ].…”
Section: Literature Review On the Use Of Icss In Bronchiectasis In Ra...mentioning
confidence: 99%
“…In most of these overlapping patients, a bronchial infection with PPMs, including P. aeruginosa , is also present and is sometimes chronic. Studies show that ICSs in COPD patients increase the risk of pneumonia, atypical mycobacteriosis, and bronchial infection with P. aeruginosa [ 102 104 ]. ICS users had suppressed IFN expression with increased exacerbation severity through greater viral loads and mucus hypersecretion.…”
Section: What Do the Guidelines Say About Using Inhaled Corticosteroi...mentioning
confidence: 99%